2021
DOI: 10.3389/fgene.2021.647996
|View full text |Cite
|
Sign up to set email alerts
|

Senataxin: A New Guardian of the Female Germline Important for Delaying Ovarian Aging

Abstract: Early decline in ovarian function known as premature ovarian aging (POA) occurs in around 10% of women and is characterized by a markedly reduced ovarian reserve. Premature ovarian insufficiency (POI) affects ~1% of women and refers to the severe end of the POA spectrum in which, accelerated ovarian aging leads to menopause before 40 years of age. Ovarian reserve refers to the total number of follicle-enclosed oocytes within both ovaries. Oocyte DNA integrity is a critical determinant of ovarian reserve since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…There are several reasons that help illustrate the mechanism of the association between advanced maternal age (>30 years old) and spontaneous abortion: (a) an age-related decline in reproductive capacity is due to the gradual decline in ovarian reserves and oocyte integrity ( 60 ); (b) more frequent chromosome separation errors lead to oocyte cell aneuploidy ( 47 ), which is believed to be the main cause of a mother's age-related spontaneous abortion; (c) there are multiple copies of the mitochondrial genome, but as we get older, different mtDNA copies will accumulate more and more mutations, so the risk of getting mutations is greater with age ( 61 ). In addition, mothers of advanced age are more likely to develop a medical condition during pregnancy, such as obesity, anemia, and diabetes ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are several reasons that help illustrate the mechanism of the association between advanced maternal age (>30 years old) and spontaneous abortion: (a) an age-related decline in reproductive capacity is due to the gradual decline in ovarian reserves and oocyte integrity ( 60 ); (b) more frequent chromosome separation errors lead to oocyte cell aneuploidy ( 47 ), which is believed to be the main cause of a mother's age-related spontaneous abortion; (c) there are multiple copies of the mitochondrial genome, but as we get older, different mtDNA copies will accumulate more and more mutations, so the risk of getting mutations is greater with age ( 61 ). In addition, mothers of advanced age are more likely to develop a medical condition during pregnancy, such as obesity, anemia, and diabetes ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that VD deficiency or insufficiency may lead to a decline in follicle quality and nondisjunction or abnormal meiosis during fertilization, which will lead to an increase in the incidence of embryo chromosome abnormalities, further resulting in spontaneous abortion. Several studies have shown that 50−70% of spontaneous abortions involve chromosomal and genetic abnormalities, 26 which may be due to the gradual decline in ovarian reserves and oocyte integrity, 27 the production of aneuploidy in abnormal chromosome meiosis during fertilization, 28 protein defects in the polymerization checkpoint of the spindle apparatus and a decrease in cohesion protein, 29 the accumulation of mtDNA copy mutations, 30 and sperm problems. Through 186 cases with ACA of medium or low titers, the study finds that there is a certain negative correlation between ACA and VD ( p < .001), which is stronger among RSA patients. Moreover, the patient's VD significantly increased, while the ACA significantly decreased after VD supplementation ( p < .001).…”
Section: Discussionmentioning
confidence: 99%
“…SNPs located in genes associated with immune and mitochondrial function as well as DNA repair and maintenance processes have been linked to early age at menopause and POI [71,72]. Among them, those involved in the regulation of DNA damage/repair and cytogenetic stability are implicated in both ovarian aging and POI [73][74][75].…”
Section: Genetic Abnormalitymentioning
confidence: 99%